The classification of measures of criminal procedure compulsion (Journal of actual problems of jurisprudence, 2019)
In this articlethe author describes the classification of measures of criminal procedure compulsion. There are given a number of classifications of the coercive procedural measures, the measures of criminal procedure compulsion: depending on a subject, which rights can be affected as a result of application of these measures, and depending on the degree of limitation of rights and individual freedoms, and depending on the aim of application.Key words: criminal procedure, the classification, measures of criminal procedure, detention, measures of suppression, judicial compulsion.